Behovsstyrd Ventilation På Kryssningsfartyg - Potential till användning och energibesparing - Nilsson, Adam; Nordlund, Ola (My University, 2016)
On board cruise vessels an important aspect for the passengers comfort is the indoor climate, however the HVAC-system necessary to condition the air on a large cruise vessel consumes a lot of energy. The cruise industry is actively working on reducing its environmental footprint and aims toward meeting the goals of IMOs EEDI initiative. This means a reduction of CO2 from propulsion by 30% by 2025. This motivates further research how the HVAC-system could be made more energy efficient. The suitability of implementing demand-controlled ventilation on board cruise vessels is examined in the following literature review. This type of ventilation strategy is sometimes used in buildings ashore. Three sub questions where used answer the main question about the suitability, and they are the following. Which type of spaces and outdoor climates is demand-controlled ventilation used ashore, if there possible to save energy on cruise vessels by using this technique, lastly the pros and cons compared to a conventional ventilation strategy is looked at. The result is based on 10 different sources and has primarily shown that the biggest energy savings ashore as been done in spaces where the number of occupants varies a lot and. This types of spaces are nightclubs, conference rooms, restaurants, shops and other public spaces. The conclusion is that the types of spaces where demand-controlled ventilation is best suited for can be found on board cruise vessels, also the climate where the majority of the cruise destinations are located is suited for using this type of technique.
Keywords: Transport; Maskinteknik; Transport; Mechanical Engineering